Neurophysiological Evidence of Enhanced Cognitive Control Following Auditory Control Enhancement (ACE) Therapy: A Pilot RCT in Schizophrenia-Spectrum Disorders with Persistent Auditory Hallucinations - Brian A. Coffman; Dylan Seebold; Jenay Kocsis; Brianna Lepore; Lauren Fowler; Hayley Rhorer; Jack Kavanagh; Fran Lopez-Caballero; Alfredo Sklar; Dean F. Salisbury (Clinical EEG and Neuroscience, 2026)
Schizophrenia (Sz) involves positive symptoms such as auditory hallucinations, paranoia, and delusions, and are commonly linked to deficits in cognitive control. These deficits appear in tasks like the A-X version of the continuous performance test (AX-CPT), which reflects reduced proactive control, and in diminished auditory steady-state responses (ASSR) during selective attention. Notably, in Sz, ASSR to sounds presented during diverted attention increases with hallucination severity. We report results from a single-blind randomized controlled trial evaluating Auditory Control Enhancement (ACE) therapy—the combination of transcranial direct current stimulation (tDCS) paired with Auditory Cognitive Control Training (ACCT)—to improve cognitive control in Sz. Ten individuals with Sz participated: six received active ACE and four received sham tDCS with ACCT. All experienced auditory hallucinations at least three days per week. ACCT consisted of three 45-min computerized sensory reaction-time sessions over three consecutive days. All procedures, including baseline and follow-up assessments, were performed over a two-week period. Electroencephalography (EEG) was collected before and after training while participants completed AX-CPT and ASSR tasks. ASSR blocks alternated between attending to auditory stimuli and ignoring them while watching a silent video. Auditory hallucinations were assessed using the PSYRATS at baseline and post-intervention. Procedures were well tolerated, and acceptability was high. Participants receiving ACE showed increased attention modulation (larger ASSR attend–ignore difference), greater beta desynchronization during proactive inhibition, and reductions in physical aspects of auditory hallucinations. In contrast, the sham group showed no changes in EEG measures or hallucination severity. These preliminary results suggest ACE may enhance cognitive control and reduce physical aspects of auditory hallucinations in Sz. ACE could represent a promising intervention for cognitive dysfunction.